2016
DOI: 10.3989/mc.2016.06415
|View full text |Cite
|
Sign up to set email alerts
|

Study of recycled concrete aggregate quality and its relationship with recycled concrete compressive strength using database analysis

Abstract: This work studies the physical and mechanical properties of recycled concrete aggregate (recycled aggregate from concrete waste) and their influence in structural recycled concrete compressive strength. For said purpose, a database has been developed with the experimental results of 152 works selected from over 250 international references.The processed database results indicate that the most sensitive properties of recycled aggregate quality are density and absorption. Moreover, the study analyses how the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 44 publications
0
24
0
1
Order By: Relevance
“…Thus, the cumulative RDEC (Ratio of Dissipated Energy Change, Equation [1]) is used to analyze the development of the damage produced in the specimen, and the Mean Damage Parameter (γ) [2] is a value used to establish a reference for the resistance to fatigue cracking of the pavement (22). Where ω n is the energy dissipation produced in loading cycle n (in J/m 3 ); and ω n+1 is the energy dissipation in loading cycle n+1 (in J/m 3 ).…”
Section: Cracking Resistance and Interlayers Adhesivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the cumulative RDEC (Ratio of Dissipated Energy Change, Equation [1]) is used to analyze the development of the damage produced in the specimen, and the Mean Damage Parameter (γ) [2] is a value used to establish a reference for the resistance to fatigue cracking of the pavement (22). Where ω n is the energy dissipation produced in loading cycle n (in J/m 3 ); and ω n+1 is the energy dissipation in loading cycle n+1 (in J/m 3 ).…”
Section: Cracking Resistance and Interlayers Adhesivenessmentioning
confidence: 99%
“…Over the last three decades, the volume of traffic in highway networks has notably increased (1). Nonetheless, in the field of construction engineering, sustainability issues have been of increasing concern (2). Therefore, the optimization of the maintenance activity of highway and road networks can be considered as a critical aspect to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…In order to produce RC, it is necessary to know the influence of the recycled aggregate's content and quality, which is usually determined by the aggregate's composition, water absorption capacity and attached mortar content (made of the source concrete) (9)(10)(11)(12)(13)(14)(15). These parameters lead to different sorts of recycled aggregates: recycled concrete aggregates (RCA), recycled ceramic aggregates or mixed recycled aggregates.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…In addition, many researchers suggested that the using of RCA to replace NA had a negative effect on the durability of concrete (6)(7)(8)(9). As reported in the literature, the weakness and high porosity of recycled aggregate, which is poorer than crushed limestone (10)(11)(12), results in a lower quality concrete. However, recycled concrete can also be used as the aggregate for new concrete if its quality is been improved (12,13).…”
Section: Introductionmentioning
confidence: 93%
“…Many researchers have reported that the old cement paste and mortar attached to the surface of the original crushed aggregate greatly influence on the quality of RCA (10)(11)(12). Table 3 shows the physical properties for the crushed limestone and the RCA used in the research.…”
Section: Aggregatesmentioning
confidence: 99%